2014
DOI: 10.3389/fncel.2014.00399
|View full text |Cite
|
Sign up to set email alerts
|

Long-term omega-3 supplementation modulates behavior, hippocampal fatty acid concentration, neuronal progenitor proliferation and central TNF-α expression in 7 month old unchallenged mice

Abstract: Dietary polyunsaturated fatty acid (PUFA) manipulation is being investigated as a potential therapeutic supplement to reduce the risk of developing age-related cognitive decline (ARCD). Animal studies suggest that high omega (Ω)-3 and low Ω-6 dietary content reduces cognitive decline by decreasing central nervous system (CNS) inflammation and modifying neuroimmune activity. However, no previous studies have investigated the long term effects of Ω-3 and Ω-6 dietary levels in healthy aging mice leaving the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 70 publications
3
18
1
Order By: Relevance
“…Assessment of cognitive flexibility revealed the role of both n-6 and n-3 FAs, but the optimal balance was quite different in younger and older children. In all models, the inclusion of the n-6:n-3 ratio resulted in more robust findings in the present study than when n-3 FAs are studied in isolation, as has been found in other studies (1,29). The importance of n-6 and n-3 FAs to cognitive function is best understood in terms of the balance between the 2 FA families.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Assessment of cognitive flexibility revealed the role of both n-6 and n-3 FAs, but the optimal balance was quite different in younger and older children. In all models, the inclusion of the n-6:n-3 ratio resulted in more robust findings in the present study than when n-3 FAs are studied in isolation, as has been found in other studies (1,29). The importance of n-6 and n-3 FAs to cognitive function is best understood in terms of the balance between the 2 FA families.…”
Section: Discussionsupporting
confidence: 85%
“…It is known that supplementing infant formula with n-6 and n-3 is more likely to produce scores that either match a breastfed reference or outperform a DHA-only group (26)(27)(28). High n-6:n-3 ratios have been shown to negatively affect working memory (29) and learning (30) performance in rodents, and to predict worse planning performance in middle childhood (1). Importantly, the cognitive functions observed (memory and executive functions) in these investigations of the n-6:n-3 ratio are subserved by the frontal cortex and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported a close relationship between microglial function and n-3 PUFAs since then. N-3 PUFA supplementation reduces microglial activation and/or phenotype alteration in models of brain development (Kuperstein et al, 2008;Madore et al, 2014;Abiega et al, 2016), respiratory system development (Tenorio-Lopes et al, 2017), healthy aging (Grundy et al, 2014), ischemia (Zhang et al, 2010;Belayev et al, 2011;Okabe et al, 2011;Eady et al, 2012aEady et al, ,b, 2014Chang et al, 2013;Zendedel et al, 2015;Jiang et al, 2016), spinal cord injury (Huang et al, 2007;Lim et al, 2013a,b;Paterniti et al, 2014;Tremoleda et al, 2016;Xu et al, 2016), Parkinson's disease (Muntane et al, 2010;Ji et al, 2012;Tian et al, 2015;Delattre et al, 2017;Mori et al, 2017), AD (Lynch et al, 2007;Hopperton et al, 2016;Serini and Calviello, 2016;Wen et al, 2016), systemic inflammation (Delpech et al, 2015b), traumatic brain injury (Pu et al, 2013;Harrison et al, 2015;Harvey et al, 2015;Desai et al, 2016), neuropathic pain model (Xu et al, 2013b;Manzhulo et al, 2015;Huang and Tsai, 2016), aging (Labrousse et al, 2012), demyelination (Chen et al, 2014), amyotrophic lateral sclerosis…”
Section: Microglia As a Target For N-3 Pufas And Spmsmentioning
confidence: 99%
“…Recently dietary interventions, particularly long-chain polyunsaturated fatty acids (LCPUFA) and curcumin, have been targeted at preventing and reversing the cognitive deficits seen with ageing. These dietary interventions have been widely shown to reduce inflammation and/or improve neurogenesis [ 81 , 82 , 83 ]. Given the strong links between increased inflammation and reduced neurogenesis with diet-induced cognitive deficits [ 10 , 11 ], the efficacy of LCPUFA and curcumin on preserving or preventing cognitive deficits will be assessed.…”
Section: Interventions To Prevent or Reverse Diet-induced Memory Dmentioning
confidence: 99%
“…As examining the mechanisms underlying the effects of diets comprising high omega-3/omega-6 ratio on cognitive performance is impossible in humans, animal models are necessary. Rodent studies have shown the cognitive benefits of a high ratio of omega-3/omega-6 PUFA supplementation on hippocampal-dependent memory tasks such as spatial recognition [ 80 , 81 , 82 ]. There are several mechanisms that are likely to regulate improved cognition following DHA supplementation.…”
Section: Interventions To Prevent or Reverse Diet-induced Memory Dmentioning
confidence: 99%